(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
A total of 111 strains of fluorescent pseudomonadеs were isolated from rice rhizosphere of different locals in the three provinces of North Iran and identified by standard methods. These isolates were tested for the production of indolylacetic acid (IAA). IAA production by studied strains in the presence of tryptophan (2 mg/mL) was recorded within the bounds of 17.69–95.89 mcg/mL. The level of IAA produced was estimated by a standard curve. Species with the largest quantities of IAA production (with rates more than average – 56.79 mcg/mL) were selected. Maximum rates of IAA production on average were 62.18 mcg/mL for Pseudomonas aeruginosa, 86.63 mcg/mL for P. putida and 68.42 mcg/mL for P. fluorescens.